Examining the Influence of Interprofessional Collaboration among Nursing Technicians, Nursing Specialists, and Radiology Professionals on Patient-Centered Care and Clinical Decision-Making: A Mixed-Methods Study - Bashirah Faleh; Ashwaq Saleh; Nooh Mahana; Zuhur Musaad; Reem Faleh Al Rashidi; Jhayer Naqa Rasam Alshammari (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective: This mixed-methods study aimed to examine the impact of interprofessional collaboration (IPC) among nursing technicians, nursing specialists, and radiology professionals on patient-centered care and clinical decision-making. Methods: A convergent parallel mixed-methods design was employed. Quantitative data was collected through surveys administered to 150 healthcare professionals. Qualitative data was gathered via semi-structured interviews with 20 purposively sampled participants. Results: Quantitative findings revealed a significant positive correlation between IPC and patient-centered care (r=0.78, p<0.01) as well as clinical decision-making (r=0.74, p<0.01). Thematic analysis of qualitative data yielded three main themes: (1) Enhanced communication and teamwork, (2) Improved patient outcomes and satisfaction, and (3) Optimized resource utilization. Conclusion: IPC among nursing and radiology staff positively influences patient-centered care and clinical decision-making. Healthcare organizations should foster an interprofessional collaborative culture to improve care quality and patient outcomes.